OFDM System Performance Evaluation under Different Fading Channels and Channel Coding using Matlab Simulink - Pratima Manhas; M.K Soni (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Orthogonal Frequency Division Multiplexing (OFDM) is a form of Multicarrier Modulation (MCM) technique in which larger bandwidth is divided into parallel narrow bands each of which is modulated by different subcarriers. All the subcarriers are orthogonal to each other and hence it reduces the interference among various subcarriers. OFDM technique is an efficient modulation technique used in certain wired and wireless application. During transmission, the transmitted signal can travel from transmitter to receiver over multiple reflective paths in case of wireless communication system which results to multipath fading and produces variation in amplitude, phase and angle of the received signal. The signal which is transmitted from BTS (base transceiver station) may undergo multiple reflections from the buildings nearby, before reaching the mobile station. This paper discusses the performance of OFDM system using various fading channels and channel coding. The parameter which is known as Bit error rate (BER) is calculated for different fading channels (AWGN, Rayleigh and Rician) for different digital modulation (BPSK, QPSK and QAM) and Channel coding(linear/ Cyclic coding).The tool which is used to evaluate  the BER parameter is Matlab Simulink.